2018
DOI: 10.1038/s41398-018-0127-5
|View full text |Cite
|
Sign up to set email alerts
|

Reverse translated and gold standard continuous performance tests predict global cognitive performance in schizophrenia

Abstract: Attentional dysfunction contributes to functional impairments in schizophrenia (SZ). Sustained attention is typically assessed via continuous performance tasks (CPTs), though many CPTs have limited cross-species translational validity and place demands on additional cognitive domains. A reverse-translated 5-Choice Continuous Performance Task (5C-CPT) for human testing—originally developed for use in rodents—was designed to minimize demands on perceptual, visual learning, processing speed, or working memory fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…This may lead to valid hypotheses about brain function that will in turn guide experiments at the neural substrate level. In addition, reverse-translation by adapting cognitive tasks from animal research to human clinical settings is a complementary approach that may start offering links between animal findings in the behavioral and neural substrate level and human symptoms (Bismark and others 2018).…”
Section: Translational Approachesmentioning
confidence: 99%
“…This may lead to valid hypotheses about brain function that will in turn guide experiments at the neural substrate level. In addition, reverse-translation by adapting cognitive tasks from animal research to human clinical settings is a complementary approach that may start offering links between animal findings in the behavioral and neural substrate level and human symptoms (Bismark and others 2018).…”
Section: Translational Approachesmentioning
confidence: 99%
“…Although BD is characterized by complex and multifaceted symptoms including elevated mood, patients who show cognitive deficits have poorer functional outcome . One dominant symptom of BD is inattention, recognized as core to cognitive deficits across psychiatric conditions . The development of pro‐attentive therapies will likely lead to more generalized cognitive improvement.…”
Section: Introductionmentioning
confidence: 99%
“…3 One dominant symptom of BD is inattention, 4 recognized as core to cognitive deficits across psychiatric conditions. 5,6 The development of pro-attentive therapies will likely lead to more generalized cognitive improvement. Unfortunately, no targeted pro-attentive treatments have been established, [7][8][9] in part due to our limited understanding of the neural systems underlying this deficit.…”
Section: Introductionmentioning
confidence: 99%
“…The 5C-CPT retains this format for target trials but – consistent with human CPTs – additionally includes non-target trials to which subjects must inhibit from responding. Further, the task has been reverse-translated for human testing and validated in clinical populations that exhibit task deficits (Young et al, 2013) comparable to those observed with traditional CPT variants (Bismark et al, In Press; Cornblatt and Keilp, 1994).…”
Section: Introductionmentioning
confidence: 99%